Force-time curve characteristics and hormonal alterations during an eleven-week training period in elite women weightlifters - Haff, G. G.; Jackson, J. R.; Kawamori, N.; Carlock, J. M.; Hartman, M. J.; Kilgore, J. L.; Morris, R. T.; Ramsey, M. W.; Sands, W. A.; Stone, M. H. (The Journal of Strength and Conditioning Research, 2008)
The purpose of this investigation was to study the effects of an 11-week training period performed by female weightlifters. Two weeks before this investigation, baseline measures for total testosterone, cortisol, and testosterone:cortisol ratio were collected. The 11-week training program consisted of the core exercises (i.e., clean, clean and jerk, and snatch) and other supplemental exercises (i.e., clean pull, snatch pull, squat, and front squat). Hormonal, isometric, and dynamic middle thigh pull force-time curve characteristics were assessed biweekly throughout the duration of the investigation, whereas volume load and training intensity were assessed weekly throughout the investigation. The testosterone:cortisol ratio of the baseline (1.19 +/- 0.64) was significantly different from the ratio of weeks 1 (0.67 +/- 0.36) and 9 (0.94 +/- 0.66). When the week-to-week values were compared, week 1 (0.67 +/- 0.36) was significantly different (P < 0.05; [eta]2 = 0.84) from week 3 (1.06 +/- 0.54). A very strong correlation (r = -0.83; r2 = 0.69) was found between the percentage change of the testosterone:cortisol ratio and volume load from weeks 1 to 11. Moderate to very strong correlations were noted between the percentage change in volume load and isometric peak force, peak force during the 30% isometric peak force trial, and peak force during the 100-kg trial during the 11 weeks of training. The primary finding of this study was that alterations in training volume load can result in concomitant changes in the anabolic-to-catabolic balance, as indicated by the testosterone:cortisol ratio, and the ability to generate maximal forces.